Sprint running performance and technique changes in athletes during periodized training - Bezodis, I. N.; Kerwin, D. G.; Cooper, S.-M.; Salo, A. I. T. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To understand how training periodization influences sprint performance and key step characteristics over an extended training period in an elite sprint training group.